2012
DOI: 10.1074/jbc.m112.362343
|View full text |Cite
|
Sign up to set email alerts
|

NAD+-dependent Sirtuin 1 and 6 Proteins Coordinate a Switch from Glucose to Fatty Acid Oxidation during the Acute Inflammatory Response

Abstract: Background: Switching from the acute early initiation to late adaptation response after TLR4 stimulation depends on SirT1. Results: Switching from glucose to fatty acid oxidation between initiation and adaptation responses requires SirT6 and SirT1. Conclusion: Bioenergy integrates metabolism and acute inflammation. Significance: Understanding bioenergy shifts during inflammation may enable development of new therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
310
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 299 publications
(332 citation statements)
references
References 38 publications
(35 reference statements)
13
310
0
2
Order By: Relevance
“…Regarding the modulator of PGC-1␣ deacetylation, we propose that SIRT1 and SIRT6 may coordinate each other. In line with this, it has been shown that SIRT1 and SIRT6 coordinate the switch from glucose to fatty acid ␤-oxidation in response to an acute inflammation (27). In addition, we observed that SIRT1 protein levels first increased at 7 days and then declined at 21 days (biphasic change).…”
Section: H354supporting
confidence: 89%
“…Regarding the modulator of PGC-1␣ deacetylation, we propose that SIRT1 and SIRT6 may coordinate each other. In line with this, it has been shown that SIRT1 and SIRT6 coordinate the switch from glucose to fatty acid ␤-oxidation in response to an acute inflammation (27). In addition, we observed that SIRT1 protein levels first increased at 7 days and then declined at 21 days (biphasic change).…”
Section: H354supporting
confidence: 89%
“…Although we did not find differences in sirtuin 1 expression in the skeletal muscle that correlate with the gene expression increase detected in fP8WR mice, we did find a significant increase in PGC-1α and in the sirtuin 1 activator AMPK in these mice. Interestingly, the activation of the sirtuin 1-AMPK-PGC-1α pathway is involved in mitochondrial biogenesis (Chen et al 2008;Liu et al 2012) and has been previously proposed as a possible target of molecular changes induced by exercise (Liu and Fielding 2011;Canto and Auwerx 2009). Indeed, evidence suggests that moderate levels of regular physical activity increase a larger number of mitochondrial biogenesis-related gene expression in aged subjects, though to a lesser extent than in younger individuals (Bori et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…also controls inflammatory response by regulating SIRT1 activity. Anti-inflammatory action of SIRT1 is exerted by promoting a switch from glycolysis to fatty acid oxidation and by deacetylating and inactivating the p65 subunit of NF-κB, thus limiting the expression of NF-κB-dependent proinflammatory genes (Yeung et al, 2004;Liu et al, 2012). Altogether, these observations strongly indicate that the metabolic state of immune cells is critical to their function: proinflammatory cells such as M1 macrophages, activated dendritic cells, and T H 17 cells are more glycolytic, whereas anti-inflammatory cells such as T reg cells and M2 macrophages have more oxidative phosphorylation (McGettrick and O'Neill, 2013).…”
Section: Citrate In Inflammationmentioning
confidence: 99%